1977
DOI: 10.1111/j.1752-7325.1977.tb02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supervised Daily Dental Plaque Removal by Children: Ii. 24 Months' Results†

Abstract: After two school years of a supervised daily plaque-removal program in school, children in the treatment group showed a significant reduction in plaque and gingival inflammation scores compared with children in the control group. However, differences between groups in terms of plaque and gingivitis scores virtually disappeared during the summer vacation. The increment of dental caries was lower in the treatment group than in the control group, but the reduction, which averaged about 20 percent, was not statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…If positive effects were found, they were limited. Small but sta tistically significant reductions in plaque and gingivitis scores reported in several studies (22,23) turn out to be non-significant when, like the present study, schools (small n) rather than the child (large n) are used as the unit of analysis, A contributory factor to the confusion regarding the effectiveness of school-based oral health education is pertaining to oral health education (21). To summarize, the oral hygiene out come effects of school-based OHE pro grammes, including the present one, are nil or at best very limited.…”
Section: Discussionmentioning
confidence: 99%
“…If positive effects were found, they were limited. Small but sta tistically significant reductions in plaque and gingivitis scores reported in several studies (22,23) turn out to be non-significant when, like the present study, schools (small n) rather than the child (large n) are used as the unit of analysis, A contributory factor to the confusion regarding the effectiveness of school-based oral health education is pertaining to oral health education (21). To summarize, the oral hygiene out come effects of school-based OHE pro grammes, including the present one, are nil or at best very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, with close supervision provided by a dedicated staff, one school-based brushing and flossing study conducted in the United States resulted in significant reductions in plaque and gingivitis scores in the treatment group and a nonsignificant reduction in dental caries increment approximating 20%"' after two years of the program. 35 Recently, Nasi36 suggested that school children in the first through sixth grades be involved in mass education programs concerning periodontal disease and its prevention to begin to create an awareness of the process at an early age. Similarly, several years ago it was suggested for the countries of the Pacific Basin that periodontal disease prevention efforts be concentrated on children of school age.37 Ancillary personnel were to be trained to carry out calculus removal.…”
Section: C22mentioning
confidence: 99%
“…The present school‐based toothbrushing (SBTB) programme was performed with the help of schoolteachers, and first graders participated in a daily SBTB with fluoride toothpaste. Few SBTB studies have addressed the possible impact on the gingival condition and on dental plaque accumulation in children (12–15). The present study aimed to test whether the gingivitis and plaque scores of 8‐ to 11‐year‐old school children who participated in a SBTB programme for 2 years were lower than those of school children who did not participate in this programme.…”
Section: Introductionmentioning
confidence: 99%